2022
DOI: 10.1111/ejn.15625
|View full text |Cite
|
Sign up to set email alerts
|

Motor point stimulation induces more robust F‐waves than peripheral nerve stimulation

Abstract: The F‐wave is a motor response induced by electrical stimulation of peripheral nerves via the antidromic firing of motor nerves, which reflects the motoneuron excitability. To induce F‐waves, transcutaneous peripheral nerve stimulation (PNS) is used, which activates nerve branches via transcutaneous electrodes over the nerve branches. An alternative method to activate peripheral nerves, that is, motor point stimulation (MPS), which delivers electrical stimulation over the muscle belly, has not been used to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
(162 reference statements)
1
0
0
Order By: Relevance
“…Also, the H‐reflex was not observed using MPS regardless of stimulus intensity, while F‐waves were recorded at relatively weaker stimulus intensity (Figure 3A,B), which were also confirmed by previous studies 6,7,23 . In addition to a lack of H‐reflexes in the present study, our group recently showed that MPS does not induce reciprocal inhibition 6 .…”
Section: Discussionsupporting
confidence: 92%
“…Also, the H‐reflex was not observed using MPS regardless of stimulus intensity, while F‐waves were recorded at relatively weaker stimulus intensity (Figure 3A,B), which were also confirmed by previous studies 6,7,23 . In addition to a lack of H‐reflexes in the present study, our group recently showed that MPS does not induce reciprocal inhibition 6 .…”
Section: Discussionsupporting
confidence: 92%